POLYHERBAL FORMULATION OPTIMIZATION FROM CLITORIA TERNATEA, ROSMARINUS OFFICINALIS AND AQUILARIA MALACCENSIS USING SIMPLEX LATTICE DESIGN - AKMAL, TUBAGUS; JULIANTI, ANDI IKA; SYAMSUDIN, SILVIA SYADZA’AH (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aimed to optimize the composition of Clitoria ternatea flowers, Rosmarinus officinalis herbs, and Aquilaria malaccensis leaves as a polyherbal formulation. Methods: The polyherbal formulation (PHF) was systematically optimized using a simplex lattice design generated by Design Expert software. The selected independent variables were the percent of C. ternatea flowers extract (X1), the percent of R. s officinalis herbs extract (X2), and the percent of A. malaccensis leaves extract (X3). The dependent variables were total phenolic contents (Y1) and 2,2-diphenyl-l-picrylhydrazyl (DPPH) radical scavenging activity (Y2). Results: The results showed that the optimum composition of PHF was C. ternatea flowers extract (10%), R. officinalis herbs extract (80%), and A. malaccensis leaves extract (10%) to obtain 135.794 mg GAE/g dried extract for total phenolic contents and 22.879 µg/ml (IC50) for DPPH radical scavenging activity. Conclusion: The findings suggest that the polyherbal formulation consisting of C. ternatea flowers (CTF), R. officinalis herbs (ROH), and A. malaccensis leaves (AML), when formulated with the optimal composition has the potential to enhance the total phenolic content and antioxidant activity.